Risk-based quality accident ranking approach using failure mechanism and Axiomatic domain mapping. (18th May 2020) - He, Yihai; Cui, Jiaming; Liu, Fengdi; Zhu, Chunling
Abstract : Manufacturers face numerous product quality accidents and thus require an effective and general approach to rank the occurred quality accidents. Therefore, a universal risk-based quality accident ranking method emphasising the importance of the accident formation mechanism is proposed in this paper to rank, analyse, and prevent occurred quality accidents comprehensively. First, the risk formation mechanism of quality accident is proposed emphatically using two typical failure mechanisms and Axiomatic domain mapping, and the structure of big quality accident data is presented on the basis of big product lifecycle data in order to provide data support for the subsequent risk analysis. Second, the accident failure cost, probability, and detectivity are adopted as the critical risk factors, which are computed using the failure cost model, extended fault tree and Axiomatic relevance tree respectively. Third, a modified risk importance index considering the relative weight of risk factors is presented to measure and rank the risk priority of quality accidents. Finally, a case study on a computer control panel accident risk analysis is conducted to verify the effectiveness of the proposed approach. Results show that the proposed method can objectively reflect the accident risk degree and provide necessary reference for accident risk mitigation.